Maleševci in Bileća’s Rudine - Pekić, Radmilo B. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
Different Vlachs katuns were located in the area of Bileća and its neighbouring area of Rudine in the Middle Ages. One of the most prominent katun clan was Maleševci and its brethren, with many branches, which is the main subject of the paper. We will begin with this clan’s first written records in the 14th century and continue until the beginning of the 16th century. Numerous documents about Vlachs Maleševci are preserved in Dubrovnik Archive, but some parts are either published or scattered in scientific writings and until now, they have never been systematised.